Asymmetric Distributions of Achromatic Bipolar Cells in the Mouse Retina - Sharpe, Zachary J.; Shehu, Angela; Ichinose, Tomomi (Frontiers in Neuroanatomy, 2022)
In the retina, evolutionary changes can be traced in the topography of photoreceptors. The shape of the visual streak depends on the height of the animal and its habitat, namely, woods, prairies, or mountains. Also, the distribution of distinct wavelength-sensitive cones is unique to each animal. For example, UV and green cones reside in the ventral and dorsal regions in the mouse retina, respectively, whereas in the rat retina these cones are homogeneously distributed. In contrast with the abundant investigation on the distribution of photoreceptors and the third-order neurons, the distribution of bipolar cells has not been well understood. We utilized two enhanced green fluorescent protein (EGFP) mouse lines, Lhx4-EGFP (Lhx4) and 6030405A18Rik-EGFP (Rik), to examine the topographic distributions of bipolar cells in the retina. First, we characterized their GFP-expressing cells using type-specific markers. We found that GFP was expressed by type 2, type 3a, and type 6 bipolar cells in the Rik mice and by type 3b, type 4, and type 5 bipolar cells in the Lhx4 mice. All these types are achromatic. Then, we examined the distributions of bipolar cells in the four cardinal directions and three different eccentricities of the retinal tissue. In the Rik mice, GFP-expressing bipolar cells were more highly observed in the nasal region than those in the temporal retina. The number of GFP cells was not different along with the ventral-dorsal axis. In contrast, in the Lhx4 mice, GFP-expressing cells occurred at a higher density in the ventral region than in the dorsal retina. However, no difference was observed along the nasal-temporal axis. Furthermore, we examined which type of bipolar cells contributed to the asymmetric distributions in the Rik mice. We found that type 3a bipolar cells occurred at a higher density in the temporal region, whereas type 6 bipolar cells were denser in the nasal region. The asymmetricity of these bipolar cells shaped the uneven distribution of the GFP cells in the Rik mice. In conclusion, we found that a subset of achromatic bipolar cells is asymmetrically distributed in the mouse retina, suggesting their unique roles in achromatic visual processing.